Globalisation's impact on local food identity in Kota Kinabalu, Sabah, Malaysia - Adilah Md Ramli; NorFatihah Muslim; Harifah Mohd Noor; Teuku Afrizal Teuku Anuar (AMER ABRA cE-Baby e-International Publishing House, Ltd, 2022)
This study aims to identify the impact of globalisation on local food identity in Kota Kinabalu, Sabah, Malaysia. 422 domestic tourists from Peninsular Malaysia as respondents and questionnaires as the research instrument. Targeting location are Tanjung Aru, Likas, and Universiti Malaysia Sabah. Results showed that only three subfactors from globalisation affected local food: globalisation awareness, localisation, and food intake factors. Regarding local food identity, the originality factor is important to respondents. There is a connection between globalisation and local food identity (p <0.05), indicating the impact of globalisation on local food by tourists.